A Kuznets adaptive approach to life expectancy at birth: an application on rising powers - Ünal, Hüseyin (2021)
This study aims to test the validness of Kuznets’ hypothesis in major rising powers between the years of 2000 and 2018 within the scope of the relationships between life expectancy at birth (throughout the paper-life expectancy-LE) and economic growth. Using panel data analysis method, we investigate if there is a curve such as Health Kuznets Curve (HKC) for life expectancy. The empirical findings indicate that the validity of HKC hypothesis could not be obtained for Brazil, Mexico, Russian Federation, South Africa and Turkey. A U-shaped relationship exists between these two variables for these countries. In other respects, we found empirical evidence of a Kuznets’curve and inverted U -shaped relations between economic growth and life expactancy for Australia, China, Indonesia and Korea. Empirical evidence also suggests that there is not any relationship between economic growth and life expectancy for India.